The role of the gut-microbiome-brain axis in metabolic remodeling amongst children with cerebral palsy and epilepsy - Peng, Ye; Chiu, Annie T. G.; Li, Vivien W. Y.; Zhang, Xi; Yeung, Wai L.; Chan, Sophelia H. S.; Tun, Hein M. (Frontiers in Neurology, 2023)
Background Epilepsy-associated dysbiosis in gut microbiota has been previously described, but the mechanistic roles of the gut microbiome in epileptogenesis among children with cerebral palsy (CP) have yet to be illustrated. Methods Using shotgun metagenomic sequencing coupled with untargeted metabolomics analysis, this observational study compared the gut microbiome and metabolome of eight children with non-epileptic cerebral palsy (NECP) to those of 13 children with cerebral palsy with epilepsy (CPE). Among children with CPE, 8 had drug-sensitive epilepsy (DSE) and five had drug-resistant epilepsy (DRE). Characteristics at enrollment, medication history, and 7-day dietary intake were compared between groups. Results At the species level, CPE subjects had significantly lower abundances of Bacteroides fragilis and Dialister invisus but higher abundances of Phascolarctobacterium faecium and Eubacterium limosum. By contrast, DRE subjects had a significantly higher colonization of Veillonella parvula. Regarding microbial functional pathways, CPE subjects had decreased abundances of pathways for serine degradation, quinolinic acid degradation, glutamate degradation I, glycerol degradation, sulfate reduction, and nitrate reduction but increased abundances of pathways related to ethanol production. As for metabolites, CPE subjects had higher concentrations of kynurenic acid, 2-oxindole, dopamine, 2-hydroxyphenyalanine, 3,4–dihydroxyphenylglycol, L-tartaric acid, and D-saccharic acid; DRE subjects had increased concentrations of indole and homovanilic acid. Conclusions In this study, we found evidence of gut dysbiosis amongst children with cerebral palsy and epilepsy in terms of gut microbiota species, functional pathways, and metabolites. The combined metagenomic and metabolomic analyses have shed insights on the potential roles of B. fragilis and D. invisus in neuroprotection. The combined analyses have also provided evidence for the involvement of GMBA in the epilepsy-related dysbiosis of kynurenine, serotonin, and dopamine pathways and their complex interplay with neuroimmune and neuroendocrinological pathways.